A significant decrease in hemoglobin concentrations may predict occurrence of necrotizing enterocolitis in preterm infants with late-onset sepsis. Issue 9 (September 2020) - Cai, Na; Fan, Wenting; Tao, Min; Liao, Wei
Objective: This study aimed to examine the clinical value of a decrease in hemoglobin concentration (HC) after the onset of sepsis for predicting occurrence of necrotizing enterocolitis (NEC) in preterm infants with late-onset sepsis. Methods: We performed a retrospective cohort study between January 2015 and January 2020. Premature neonates (gestational age <37 weeks) with late-onset sepsis (age >3 days) were enrolled. According to the degree of reduction in HC, neonates were divided into the non-decrease group, mild decrease group, and severe decrease group. Demographic data, perinatal conditions, blood cell count analysis, blood culture, and treatment measures were compared. Results: Eighty premature infants with sepsis were studied. The mortality rate and incidence of NEC were significantly higher in the severe decrease group than in the non-decrease and mild decrease groups. Significant differences were observed in the decrease in HC, red blood cell transfusion, and ventilator application between the NEC and non-NEC groups. A significant decrease in HC was an independent risk factor for NEC in preterm infants with sepsis. Conclusion: A significant decrease in HC is an independent risk factor for NEC and may predict the occurrence of NEC in preterm infants with sepsis.